2001
DOI: 10.1007/s003300101121
|View full text |Cite
|
Sign up to set email alerts
|

Duplex ultrasonographic study of the renal arteries before and after renal artery stenting

Abstract: The aim of our study was to evaluate feasibility and accuracy of colour-coded duplex US in the detection of renal artery stenosis before and after stenting. Eighty-four patients (23 women, 61 men; mean age 64 years) with significant renal artery stenosis were studied with Doppler US, before and after stenting. A combined anterior and translumbar approach was used to visualise the renal arteries. Renal artery stenosis and in-stent restenosis were proved by the increase of renal peak systolic velocity (PSV) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 23 publications
2
28
1
3
Order By: Relevance
“…The mean values ± SD of renal artery PSV presented a significant statistical difference (p < 0.005) between the groups with RAS 0-59% and RAS 60-99% (see table 3) in agreement with the results obtained in various publications 22,23,24 .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The mean values ± SD of renal artery PSV presented a significant statistical difference (p < 0.005) between the groups with RAS 0-59% and RAS 60-99% (see table 3) in agreement with the results obtained in various publications 22,23,24 .…”
Section: Discussionsupporting
confidence: 80%
“…This result agrees with the findings of other authors who also demonstrated that by reducing the RAR cut-off point to values between 2.5 and 3.2, the sensitivity was increased which lowered the occurrence of false negatives 24,26,27,28 . On the other hand, Miralles and associates demonstrated that the RAR with a cut-off point of 3.3 presented low sensitivity and that this parameter did not contribute to lesion diagnosis when compared to the individual use of PSV 22 .…”
Section: Cardoso E Cols Direct Duplex Scanning Parameters In the Diasupporting
confidence: 83%
See 1 more Smart Citation
“…The PSV within the stenosis decreases. The sensitivity and specificity of the PSV measurement for in-stent restenosis reach 90 and 93%, respectively [7]. Thus, restenosis can reliably be diagnosed by direct measurement of in-stent flow.…”
Section: Discussionmentioning
confidence: 99%
“…Its parameters of direct vascular and indirect renoparenchymal scanning have been thoroughly evaluated for diagnostic sensitivity and specificity [6]. The immediate effects of renal artery stenting on the results of duplex scanning are well documented [7, 8]. Studies on ultrasound follow-up after renal artery intervention have mostly been done either in angioplasty without stenting [9] or were limited by the small patient number (18–28 patients) [8, 10] or short follow-up time [11].…”
Section: Introductionmentioning
confidence: 99%